2020
DOI: 10.1186/s13643-020-01516-1
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines to prevent COVID-19: a protocol for a living systematic review with network meta-analysis including individual patient data (The LIVING VACCINE Project)

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19) which has rapidly spread worldwide. Several human randomized clinical trials assessing potential vaccines are currently underway. There is an urgent need for a living systematic review that continuously assesses the beneficial and harmful effects of all available vaccines for COVID-19. Methods/design We will conduct a living systematic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 82 publications
0
52
0
Order By: Relevance
“…The previous literature has already demonstrated that it is necessary to evaluate the e cacy and possible side effects of each of the many vaccines against COVID-19 separately (27). In our case, given the difference observed between the levels of intention to be vaccinated with each vaccine, prediction models were tested for each one separately.…”
Section: Discussionmentioning
confidence: 99%
“…The previous literature has already demonstrated that it is necessary to evaluate the e cacy and possible side effects of each of the many vaccines against COVID-19 separately (27). In our case, given the difference observed between the levels of intention to be vaccinated with each vaccine, prediction models were tested for each one separately.…”
Section: Discussionmentioning
confidence: 99%
“…This review aims to assess the use of Trial Sequential Analysis in the current body of systematic reviews and meta-analyses. Trial Sequential Analysis offers important pieces of information [4,15,29] and provides more stringent planning of how to calculate the DARIS and interpret the imprecision in GRADE [16,18,20,[29][30][31][32][33] than present recommendations regarding the calculation of optimal information size and assessment of imprecision in GRADE [27]. However, the method is currently not a mandatory part of Cochrane Reviews.…”
Section: Discussionmentioning
confidence: 99%
“…We will downgrade imprecision in GRADE by two levels if the accrued number of participants is below 50% of the diversity-adjusted required information size (DARIS), and one level if between 50% and 100% of DARIS. We will not downgrade if the cumulative Z-curve crosses the monitoring boundaries for benefit, harm or futility, or DARIS is reached [88]. The findings for primary outcomes will be presented in a summary of findings table where each GRADE domain will be presented for trials contributing data to the meta-analyses for the prespecified outcomes [58,89].…”
Section: Gradementioning
confidence: 99%